2022
DOI: 10.1073/pnas.2212533119
|View full text |Cite
|
Sign up to set email alerts
|

The human pathobiont Malassezia furfur secreted protease Mfsap1 regulates cell dispersal and exacerbates skin inflammation

Abstract: Malassezia form the dominant eukaryotic microbial community on the human skin. The Malassezia genus possesses a repertoire of secretory hydrolytic enzymes involved in protein and lipid metabolism which alter the external cutaneous environment. The exact role of most Malassezia secreted enzymes, including those in interaction with the epithelial surface, is not well characterized. In this study, we compared the expression level of secreted proteases, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Recent interesting study reported that MGSAP1 was upregulated in atopic and seborrheic dermatitis skin. Furthermore, this SAP play a pivotal role in fungal skin colonization and tissue inflammation in diseased skin tissue [ 24 ]. In our present work, pH is another factor which could control the expression of SAP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent interesting study reported that MGSAP1 was upregulated in atopic and seborrheic dermatitis skin. Furthermore, this SAP play a pivotal role in fungal skin colonization and tissue inflammation in diseased skin tissue [ 24 ]. In our present work, pH is another factor which could control the expression of SAP.…”
Section: Discussionmentioning
confidence: 99%
“…S18 ). A recent study revealed that MFSAP2 expression is essentially undetectable in M. furfur CBS14141 WT, whereas MFSAP1 (GLX27_000216), which lies adjacent to MFSAP2 in the genome, is the most highly expressed SAP gene (46). Our data confirmed that MFSAP1 is highly expressed but not differentially expressed in both mutant and WT strains (GLX27_000216; Datasets S2 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…Our data confirmed that MFSAP1 is highly expressed but not differentially expressed in both mutant and WT strains (GLX27_000216; Datasets S2 and S3). M. furfur MFSAP1 seems to play an essential role in fungal skin colonization and tissue inflammation, and a compensatory expression of the other SAP genes was not observed when MFSAP1 was deleted (46). Therefore, the increased expression of MFSAP2 and three lipase genes in the A on B off and “solo” strains could represent a life cycle stage-specific response possibly associated with hyphal growth during sexual development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Microsporum canis Sub3 subtilisin, a cell-mediated immune response was demonstrated in the experimentally infected guinea pig model, and for the extracellular metalloproteinase Mep3 of the same species, an antibody response was observed, although neither protease was protective in the vaccination trials [ 111 , 112 , 113 , 114 ]. In addition, the secretory aspartyl protease Mfsap1 from an opportunistic cutaneous pathogen Malassezia furfur has been recently indicated as strongly contributing to the development of inflammation in barrier-compromised murine skin, and the mechanisms may involve a direct interaction of protease with the host, or the Mfsap1-dependent modification of fungal cell surface hydrophobicity [ 115 ]. An endemic fungus Paracoccidioides brasiliensis has also been reported to produce serine and cysteine proteases that trigger IL-6 and IL-8 secretion by lung epithelial cells in PAR1- and PAR2-dependent manners [ 116 ], and representatives of the former group of Paracoccidioides proteases have also been demonstrated to have antigenic properties [ 117 ].…”
Section: Fungal Proteases As Allergensmentioning
confidence: 99%